2019
DOI: 10.1002/slct.201900622
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimetallic Ferrocenyl Dithiophosphonate Complexes of Nickel(II), Zinc(II) and Cadmium(II) as Sensitizers for TiO2‐Based Dye‐Sensitized Solar Cells

Abstract: The formation, characterization, and dye sensitized solar cell application of nickel(II), zinc(II) and cadmium(II) ferrocenyl dithiophosphonate complexes were investigated. The multidentate monoanionic ligand [S 2 PFc(OH)] À (L1) was synthesized. The reaction between metal salt precursors and L1 produced Ni(II) complexes of the type [Ni{S 2 P(Fc)(OH)} 2 ] (1) (molar ratio 1:2), and a tetranickel(II) complex of the type [Ni 2 {S 2 OP(Fc)} 2 ] 2 (2) (molar ratio (1:1). It also produced a Zn(II) complex [Zn{S 2 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Co-sensitization with N719 led to slightly enhanced performances with respect to N719 alone for the Zn(II) and Cd(II)-based dyes. 254 Several examples of derivatives of 1,1 0 -bis(diphenyl)phosphanoferrocene (dppf) have been trialled as sensitizers in DSCs. 255,256 The dimetallic complexes [Ni(dppf)(S 2 C]C(H)NO 2 )] and [Ni(dppf)(S 2 C]C(COMe) 2 )] absorb in the visible with maxima ca.…”
Section: The Holy Grail: Iron In Dscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-sensitization with N719 led to slightly enhanced performances with respect to N719 alone for the Zn(II) and Cd(II)-based dyes. 254 Several examples of derivatives of 1,1 0 -bis(diphenyl)phosphanoferrocene (dppf) have been trialled as sensitizers in DSCs. 255,256 The dimetallic complexes [Ni(dppf)(S 2 C]C(H)NO 2 )] and [Ni(dppf)(S 2 C]C(COMe) 2 )] absorb in the visible with maxima ca.…”
Section: The Holy Grail: Iron In Dscsmentioning
confidence: 99%
“…A number of dithiolate and dithiocarbamate complexes of nickel and bearing peripheral ferrocenyl units were described earlier in this review. [254][255][256] Zhang et al reported the formation and structure of the 1Dcoordination polymer [Ni(en) 2 (azobc)] n (H 2 azobc ¼ azobenzene-4,4 0 -dicarboxylic acid) (Fig. 14).…”
Section: Nickelmentioning
confidence: 99%
“…An alternative way to multi-ferrocenyl compound is using phosphorus acids derivatives, containing ferrocene fragments. These ferrocene derivatives can be easily accessed via low cost syntheses with good yields [14,15]. It was demonstrated that ferrocene containing phosphate molecules can be successfully used for the construction of multi-step multi-electron redox systems [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Proposed mechanism for the formation of macrocycles 46, 47, and 50. sensitizers for TiO 2 -based DSSC (Dye-Sensitized Solar Cells). [21] Unlike their previous report [20] they proceeded with water instead of alcohol to compose ferrocenyl dithiophosphonate ligand 69. Hydrated Ni(II), Cd(II), and anhydrous Zn(II) salts reacted with 69 in different molar ratios in THF to furnish four unique architectures (70-73) (Scheme 24).…”
Section: Decoration Of Metal Incorporated Scaffoldsmentioning
confidence: 89%
“…Another interesting report was provided by the same group where they invented new nickel(II), zinc(II), and cadmium(II) complexes bearing the FcLR ligand capable of acting as sensitizers for TiO 2 ‐based DSSC (Dye‐Sensitized Solar Cells) . Unlike their previous report they proceeded with water instead of alcohol to compose ferrocenyl dithiophosphonate ligand 69 .…”
Section: Decoration Of Metal Incorporated Scaffoldsmentioning
confidence: 99%